Adaptive function and phylogenetic significance of novel skeletal features of a new Devonian microconchid tubeworm (Tentaculita) from Wyoming, USA. (January 2022) - Zatoń, Michał; Hu, Mingxi; di Pasquo, Mercedes; Myrow, Paul M.
Abstract: A new genus and species of microconchid tubeworm, Aculeiconchus sandbergi n. gen. n. sp., is described from the Givetian (Devonian) Maywood Formation of Cottonwood Canyon, Wyoming, USA. It possesses unique hollow spines of various lengths on the tube underside, a position previously undocumented for these fossils. Like some cyclostome bryozoans possessing basal tubular extensions, the basal spines of Aculeiconchus n. gen. were presumably also used for fixation to flexible substrata, e.g., algal thalli, which is a previously undocumented adaptive strategy in microconchids. Together with other skeletal features, such basal spines could suggest that 'lophophorate' microconchids, unlike the other tentaculitoids, might be phylogenetically not as distant from bryozoans as previously thought. The Maywood Formation, which contains a few-millimeters thick, monospecific shell accumulation of the microconchids described herein, records deposition in an estuarine brackish setting within narrow channels that were cut into underlying strata. The microconchids were opportunistic taxa that repeatedly colonized these salinity-stressed estuarine channels, leading to a series of adaptive innovations, including colonization of plant stems during the Early Devonian (Beartooth Butte Formation) and possibly flexible, soft-algal substrata during the Middle Devonian (Maywood Formation, this study). Tectonic quiescence during the Early and Middle Devonian indicates that erosion and subsequent deposition of the Maywood and the underlying Beartooth Butte Formation channels were responses to major eustatic events. Over a span of nearly 30 Myr, channels were cut successively during lowstand conditions and a distinctive faunal assemblage with microconchids tracked marine transgressions into the channels. UUID: http://zoobank.org/394c8b32-d5e7-411e-8e56-6fb9f55bbb8a